Linking up with video. Perspectives on interpreting practice and research - Salaets, Heidi; Brône, Geert (Benjamins Translation Library (BTL);, 2020)
This volume is intended as an innovating reader for both interpreting practitioners as well as scholars, engaging with the multifaceted question addressed in the title “Why linking up with video?”. The chapters in this volume deal with this question from different perspectives. On the one hand, the volume continues the ongoing discussion on the pros and cons of video-based interaction for the interpreting profession, exploring the implications and applications when interpreters and their clients link up through video technology. On the other hand, the chapters also explore the potential of video technology for research on interpreting, hence raising the question in which way high-quality video recordings of interpreters in the booth, participants involved in interpreter-mediated talk, etc. may be instrumental in gaining new insights. In this sense, the volume strongly ties in with the fast-growing field of multimodal (interaction) studies, which makes use of video recordings to study the relationship between verbal and nonverbal resources, such as gestures, postural orientation, gaze and head movements, in the construction of meaning in communication.